NILAI-NILAI PENDIDIKAN ISLAM DALAM AL-QUR’AN SURAH IBRAHIM AYAT 7 PERSPEKTIF TAFSIR AL-MISHBAH KARYA M. QURAISH SHIHAB - Nurul Faizah; Sumar’in Sumar’in; Ahmad Rathomi (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This research aims to determine the value of Islamic education in the Al-Qur'an, Surah Ibrahim verse 7 according to the interpretation of al-Mishbah. The questions to be answered through this research are: 1) What are the values of Islamic education in surah Ibrahim verse 7 according to the tafsir al-Mishbah by M. Quraish Shihab. 2) What is the relevance of Al-Qur'an surah Ibrahim verse 7 from the perspective of the interpretation of Al-Mishbah by M. Quraish Shihab in everyday life. The approach used in this research is a qualitative approach with a type of library research, namely studying the text in depth, both regarding its content and meaning, as well as the structure and discourse contained in the main source, namely the Al-Qur'an, Surah Ibrahim verse 7 and its interpretation. al-Mishbah by M. Quraish Shihab. The results of this research show that: 1) The values of Islamic education contained in surah Ibrahim verse 7 according to the interpretation of al- Mishbah include a) Values of Aqidah (Tauhid) b) Moral Values, and c) Sharia Values. 2) The relevance of Surah Ibrahim verse 7 in everyday life is that by being grateful you will gain peace of mind within yourself, improve the quality of life, increase well- being in life, and can become a positive suggestion in yourself so that it makes a person's psychological condition good, and becomes being strong in facing a problem that makes a person's condition healthier physically and spiritually.